Mapping quantitative resistance to septoria tritici blotch in spelt wheat - Simón, María Rosa (2010)
The foliar wheat disease septoria tritici blotch can cause significant yield losses. A source of resistance has been mapped on chromosome 7D of spelt wheat, Triticum aestivum L. subsp. spelta (L.) Thell. The microsatellite-based genetic map was constructed from a set of 87 single-chromosome recombinant doubled-haploid lines bred from the cross between the landrace ‘Chinese Spring’ and a ‘Chinese Spring’-based line carrying chromosome 7D from spelt wheat. Two regions of the chromosome were associated with isolate-specific QTL expressed one at the seedling and another at the adult plant stage. The seedling resistance locus QStb.ipk-7D1 was found in the centromeric region of chromosome 7D, which corresponds to the location of the major resistance genes Stb4 originating from bread wheat cultivar ‘Tadinia’ and Stb5 originating from Triticum tauschii. The adult resistance locus QStb.ipk-7D2 was found on the short arm of chromosome 7D in a similar position to the locus Lr34/Yr18 known to be effective against multiple pathogens. Composite interval mapping confirmed QStb.ipk-7D1 and QStb.ipk-7D2 to be two distinct loci.